The Positive Effects of Exogenous Pancreatin on Growth Performance, Nutrient Digestion and Absorption, and Intestinal Microbiota in Piglets - Liu, Xin; Huang, Xiangyun; Fu, Yang; Wang, Yizhen; Lu, Zeqing (Frontiers in Physiology, 2022)
Pancreatin secretion is dramatically decreased over time after weaning, thus affecting the utilization of nutrients in piglets. Therefore, exogenous pancreatin is expected to alleviate this situation. This experiment was conducted to investigate the effects of exogenous pancreatin on the growth performance, nutrient digestion and absorption, and intestinal microbiota of piglets. One hundred eighty piglets (Duroc × Landrace × Yorkshire, 40 days) were randomly allotted to three treatments (basal diets supplemented with 0, 250, or 500 mg/kg pancreatin) with three replicate pens per treatment and 20 piglets per pen. Compared with the control diet, dietary 500 mg/kg pancreatin significantly increased (p < 0.05) the average daily gain (ADG) and the apparent digestibility of crude protein and crude fat of piglets. Regarding endogenous enzymes, pancrelipase activity in the pancreas, duodenal mucosa, and small intestinal digesta as well as trypsin activity in the jejunal digesta were increased in piglets fed a diet supplemented with 500 mg/kg pancreatin (p < 0.05). Moreover, amylopsin activity was significantly strengthened in the pancreas, duodenal mucosa, and digesta in piglets fed a diet with 500 mg/kg pancreatin (p < 0.05). The mRNA expression of nutrient transporters, including oligopeptide transporter-1 (PepT1), excitatory amino acid transporter-1 (EAAC1), cationic amino acid transporter-1 (CAT1), sodium glucose cotransporter-1 (SGLT1), glucose transporter-2 (GLUT2), and fatty acid transporter-4 (FATP4), in the jejunum significantly increased after dietary supplementation with 500 mg/kg pancreatin (p < 0.05). An increased villus height-to-crypt depth ratio of the ileum was observed in the 500 mg/kg pancreatin-treated group (p < 0.05). The composition of the colonic microbiota modulated by the addition of 500 mg/kg pancreatin was characterized by an increased relative abundance of Lactobacillus (p < 0.05), and the predicted functions revealed that 500 mg/kg pancreatin supplementation enhanced the functional abundance of genetic information processing in colonic microorganisms and environmental information processing. Our findings suggested that the addition of 500 mg/kg pancreatin improved the growth performance of piglets, improved intestinal structure, and modulated the colon microbiota, thereby increasing nutrient digestibility.